Surgical management of stage T1 renal tumours in Canadian academic centres - Lavallée, Luke T.; Tanguay, Simon; Jewett, Michael A.; Wood, Lori; Kapoor, Anil; Rendon, Ricardo A.; Moore, Ronald B.; Lacombe, Louis; Kawakami, Jun; Pautler, Stephen E.; et al. (Canadian Urological Association Journal, 2015)
Introduction: The proportion of patients with stage 1 renal tumours receiving partial nephrectomy is considered a quality of care indicator. The objective of this study was to characterize surgical practice patterns at Canadian academic institutions for the treatment of these tumours. Methods: The Canadian Kidney Cancer Information System (CKCis) is a multicentre collaboration of 13 academic institutions in Canada. All patients with pathologic stage T1 renal tumours in CKCis were identified. Descriptive statistics were performed to characterize practice patterns over time. Associations between patient, tumour, and treatment factors with the use of partial nephrectomy were determined. Results: From 1988 to April 2014, 1453 patients with pathologic stage 1 renal tumours were entered in the CKCis database. Of these, 977 (67%) patients had pT1a tumours; of these, 765 (78%) received partial nephrectomy. Of the total number of patients (1453), 476 (33%) had pT1b tumours; of these, 204 (43%) received partial nephrectomy. The use of partial nephrectomy increased over time from 60% to 90% for pT1a tumours and 20% to 60% for pT1b tumours. Stage pT1b (relative risk [RR] 0.56, 95% confidence interval [CI] 0.50–0.63) and minimally invasive surgical approach (RR 0.78, 95% CI 0.73–0.84 for pT1a and RR 0.23, 95% CI 0.17–0.30 for pT1b) were associated with decreased use of partial nephrectomy. Most patient factors including age, gender, body mass index, hypertension, and renal function were not significantly associated with use of partial nephrectomy (p > 0.05). Conclusion: Almost all pT1a and most pT1b renal tumours managed surgically at academic centres in Canada receive partial nephrectomy. The use of partial versus radical nephrectomy appears to occur independently of patient age and comorbid status, which may indicate that urologists are performing partial nephrectomy whenever technically feasible based on tumour factors. Although the ideal proportion patients receiving partial nephrectomy cannot be determined, treatment distribution observed in this cohort may indicate an achievable case distribution among experienced surgeons.